INTERNAL CLADDING LAYER INFLUENCE ON THE DEBONDING OF HAT-STRINGER STIFFENED COMPOSITE PANELS UNDER AXIAL COMPRESSION (MT) - YUAN Fei; LIU Fu; CHAI YaNan; CHEN XiangMing; LIN GuoWei; LI XinXiang (Jixie qiangdu)
Debonding between flange and skin is the dominate failure mode of stiffened composite panels which are widely used in modern aircraft. The influence of internal cladding layer in hat stringer on the onset of debonding is investigated experimentally and numerically. Cohesive elements are used to simulate the adhesive layer between skin and flange and Hashin’s failure criterion is adopted to determine damage initiation of composite layers in the numerical simulations. The process of damage initiation, propagation and failure of the stiffened composite panels was simulated in detail. A good agreement between tests and numerical prediction was observed.